Barriers to Tuberculosis Program in Nepal During COVID-19 Pandemic: Health Service Providers’ Perspectives (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2023)
Background:  Tuberculosis remains a major public health program in Nepal. The current COVID-19 pandemic has led to a change in prioritization which has affected many aspects including the functioning of tuberculosis control programs. The study aimed to assess the challenges due to COVID- 19 pandemic on the management of tuberculosis.Methods: We employed a qualitative study design to determine health service providers' perspectives on barriers to TB programs during the COVID-19 pandemic. A total of 21 health offices and 21 municipality offices were selected, three each in seven provinces of Nepal. A total of 57 key informant interviews were conducted with the health coordinators at the local level and health service providers (TB focal person and health office in charge) at the province level. Using inductive and deductive coding, a thematic analysis approach was used for data analysis.Results: Five themes and eight sub-themes emerged from the analysis. Health service delivery was hampered by a shortage of human resources, strict restrictions on mobility during the lockdown, and challenges in managing TB and COVID-19 simultaneously. The health service providers experienced an increased workload, leading to less focus on regular TB programs including disruption in reporting, recording, field-based activities, and training programs, and disruption in logistic management, impacting the quality of care. Leadership and governance issues were evident in hampered regular schedules of monitoring, supervision, and poor communication among government tiers.Conclusion: Implementation of TB programs was challenging due to the COVID-19 pandemic. The preparedness for such circumstances needs to be done considering the perspectives of the health service providers.